The Old Drift : A Novel - Serpell, Namwali 1980- (London Hogarth, 2019)
On the banks of the Zambezi River, a few miles from the majestic Victoria Falls, there was once a colonial settlement called The Old Drift. Here begins the epic story of a small African nation, told by a mysterious swarm-like chorus that calls itself man's greatest nemesis. The tale? A playful panorama of history, fairytale, romance and science fiction. The moral? To err is human.
The grandmothers -- The mothers -- The children.
Keywords: Families -- Fiction -- Zambia; FICTION / Literary; Zambia -- Fiction; Zambia; Fiction; Fantasy fiction; Fantasy fiction; Historical fiction